Ammonia emissions, impacts, and mitigation strategies for poultry production: A critical review. (15th February 2023) - Bist, Ramesh Bahadur; Subedi, Sachin; Chai, Lilong; Yang, Xiao
Abstract: Confined animal feeding operations (CAFOs) are the main sources of air pollutants such as ammonia (NH3 ) and greenhouse gases. Among air pollutants, NH3 is one of the most concerned gasses in terms of air quality, environmental impacts, and manure nutrient losses. It is recommended that NH3 concentrations in the poultry house should be controlled below 25 ppm. Otherwise, the poor air quality will impair the health and welfare of animals and their caretakers. After releasing from poultry houses, NH3 contributes to the form of fine particulate matters in the air and acidify soil and water bodies after deposition. Therefore, understanding the emission influential factors and impacts is critical for developing mitigation strategies to protect animals' welfare and health, environment, and ecosystems. This review paper summarized the primary NH3 emission influential factors, such as how poultry housing systems, seasonal changes, feed management, bedding materials, animal densities, and animals' activities can impact indoor air quality and emissions. A higher level of NH3 (e.g., >25 ppm) results in lower production efficiency and poor welfare and health, e.g., respiratory disorder, less feed intake, lower growth rates or egg production, poor feed use efficiency, increased susceptibility to infectious diseases, and mortality. In addition, the egg quality (e.g., albumen height, pH, and condensation) was reduced after laying hens chronically exposed to high NH3 levels. High NH3 levels have detrimental effects on farm workers' health as it is a corrosive substance to eyes, skin, and respiratory tract, and thus may cause blindness, irritation (throat, nose, eyes), and lung illness. For controlling poultry house NH3 levels and emissions, we analyzed various mitigation strategies such as litter additives, biofiltration, acid scrubber, dietary manipulation, and bedding materials. Litter additives were tested with 50% efficiency in broiler houses and 80–90% mitigation efficiency for cage-free hen litter at a higher application rate (0.9 kg m −2 ). Filtration systems such as multi-stage acid scrubbers have up to 95% efficiency on NH3 mitigation. However, cautions should be paid as mitigation strategies could be cost prohibitive for farmers, which needs assistances or subsidies from governments. Highlights: Ammonia emissions from poultry production are environmental concerns. High levels of NH3 can impact animals and their caretakers' health. Emission influential factors in different poultry houses were categorized. Mitigation strategies for NH3 control were summarized.